2023
DOI: 10.1109/access.2023.3251988
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Data Augmentation Method for Improved Visual Crack Detection Using Generative Adversarial Networks

Abstract: Condition monitoring and inspection are core activities for assessing and evaluating the health of critical infrastructure spanning from road networks to nuclear power stations. Defect detection on visual inspections of such assets is a field that enjoys increasing attention. However, data-based models are prone to a lack of available data depicting cracks of various modalities and present a great data imbalance. This paper introduces a novel data augmentation technique by deploying the CycleGan Generative Adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Penava and Pascal [75] have utilized GANs to generate synthetic EEG data, demonstrating the potential of GANs to expand the breadth of available EEG datasets for model training. Similarly, Habashi and Ahmed [76] have employed GANs to produce synthetic images of EEG spectra, which can be particularly useful for tasks involving spectral analysis.…”
Section: ) Generative Modelsmentioning
confidence: 99%
“…Penava and Pascal [75] have utilized GANs to generate synthetic EEG data, demonstrating the potential of GANs to expand the breadth of available EEG datasets for model training. Similarly, Habashi and Ahmed [76] have employed GANs to produce synthetic images of EEG spectra, which can be particularly useful for tasks involving spectral analysis.…”
Section: ) Generative Modelsmentioning
confidence: 99%
“…These algorithms, renowned for their CNN-based architectures, excel in image-to-image predictions and have found utility in the analysis of solid structures in tasks ranging from field predictions [16] and defect detection [26] to comprehensive fracture pattern analysis. More advanced methods like Generative Adversarial Networks (GANs) [27], cycle-consistent adversarial neural networks (CycleGAN) [28], and conditional generative adversarial networks (cGAN) [29] have also been used for the generation of images that predict field data [12,[30][31][32]. As an example, Hoq et al [12] used several machine learning methods such as artificial neural networks (ANNs) [33], CNNs, and cGAN for the prediction of stress fields in structures with random heterogeneity and concluded that CNNs and cGAN can outperform classical machine learning methods (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Crack segmentation in roads has gained increasing attention in recent years through convolutional neural networks (CNNs) [15]. CNNs can obtain hierarchical representations from large datasets to capture complex image patterns and features [16].…”
Section: Introductionmentioning
confidence: 99%